OC-040 RETAINER I (RETENTION OF URINE AFTER INGUINAL HERNIA ELECTIVE REPAIR), A PROSPECTIVE, INTERNATIONAL, MULTICENTRE COHORT STUDY. (13th October 2022) - Croghan, S; Fullard, A; Fleming, C; ,
Abstract: Aim: Post-operative urinary retention (POUR) is a recognised complication of inguinal hernia repair (IHR). Reported incidence is variable, and reporting of risk factors, contradictory. We aimed to report the rate, risk factors and impact of POUR post IHR. Methods: A prospective international observational study was performed with 4 week data collection from each centre (March-November 2021). Patients undergoing elective open/minimally-invasive IHR were eligible. Exclusion criteria included a urethral catheter at baseline. Preoperative/intraoperative/postoperative variables were analysed and data recorded via REDCap. Multivariate analysis was performed with a primary outcome of development of POUR. Secondary outcomes were risk factors for, and implications of, POUR. Results: 4, 153 patients (205 centres; 35 countries) were registered. Mean age was 54.7 years (18–95) and BMI 26.5 (16–6). 80.4% (n=3167) were performed open and 17% (n=674) minimally-invasively. The overall rate of POUR was 5.8% (n=225) and increasd >9% in male patients aged >65 years old. Risk factors associated with POUR included: higher preoperative IPSS scores (mean 9.4 vs 5.6 in non-POUR cohort, p<0.001), diagnosis of BPH (p<0.001), pre-operative constipation (p=0.009) defined as no bowel opening for two days pre-operatively and pre-operative post void residual volumes (<0.001). 37% of patients developing POUR required an unplanned hospital admission. Conclusion: This study suggests a global POUR rate of approximately 5% following elective IHR and confirm a significant impact of POUR on patients and hospital services. Findings highlight several risk factors and confirm the IPSS score as a potential risk stratification tool.